Global trends and burden of dental caries in permanent teeth (1990–2021) - Lina Zhang; Siao Zhao (Medicine, 2026)
This study aims to analyze the incidence, prevalence, and years lost due to disability (YLDs) of permanent dental caries using Global Burden of Disease data, and to investigate its correlation with socioeconomic indicators. Data were obtained from the Global Burden of Disease (GBD) 2021 database, covering variations by age, sex, and geographic region. A retrospective epidemiological analysis was conducted using descriptive statistics, autoregressive integrated moving average (ARIMA) modeling, and correlation analyses between SDI and estimated annual percentage change (EAPC). Data visualization and statistical analyses were performed using R software. The global burden of dental caries has increased significantly, with a particular emphasis on low-SDI regions. The incidence rates of high-SDI countries were reduced as a consequence of enhanced access to dental care and fluoridation policies. The prevalence of caries among males increased modestly, with the maximum prevalence observed among those aged 15 to 24 years. A negative correlation was found between EAPC and SDI levels, indicating that the disease burden grew more rapidly in low-income regions. The rising global burden of dental caries, especially in low-SDI regions, highlights the urgent need for equitable oral health policies, enhanced access to dental care, and community-based preventive strategies to reduce global disparities.